ONE-STEP CONVERSION OF EUGENOL TO METHYL ISOEUGENOL USING MICROWAVE IRRADIATION IN SOLVENT-FREE CONDITIONS - Marcellino Rudyanto; Lanny Hartanti (Indonesian Journal of Chemistry, 2006)
A research on conversion of eugenol to methyl isoeugenol via one-step reaction with microwave irradiation has been carried out. Mixtures containing eugenol, sodium or potassium carbonate as solid support, with or without sodium or potassium hydroxide as base, with or without tetrabutylammonium bromide as phase transfer catalyst, with dimethyl sulfate as the methylating agent were irradiated in a domestic microwave oven for 20 - 50 seconds. It was revealed that one-step methylation and isomerization required combinations of sodium or potassium hydroxide base and tetrabutylammonium bromide. Without combination of base and TBAB only one product, i.e. methyl eugenol, was formed.